Riau Provincial General Election Commission's Efforts to Increase Political Participation of Disabled Voters in The 2024 Election - Ningsih, Sunarti Ayu; Yandra, Alexsander; Ruslyhardy; Sudaryanto (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
One of the successes of elections is the high level of participation. High participation guarantees the legitimacy of the government and protects the voting rights of citizens, including groups of people with disabilities. The research method used was a qualitative method with a descriptive approach and the technique for determining informants used a purposive technique. Based on research results, it shows that the Riau Province KPU has made efforts to increase the participation of disabled voters in the 2024 elections. However, these efforts have not been optimal. In carrying out its efforts, the Riau Province KPU still has obstacles so that the participation rate of disabled voters in Riau Province is still very low. The roles that have been carried out by the Riau Province KPU are conducting outreach to disabled voters, coordinating between agencies, forming democracy volunteers, opening up opportunities to organize general elections for people with disabilities, and creating accessible general elections. The obstacles faced by the Riau Province KPU in increasing the participation of people with disabilities in the 2024 elections are influenced by family factors, economic factors, and finally budget factors.